Building the Next Generation: Sowing Hope through Assistance to Orphans in RW 10 Semanan, Kali Deres District, West Jakarta - Andri Maulana; Ahmad Baizuri (International Research and Development for Human Beings (IRDH), 2025)
The orphanage assistance program in RW 10 Semanan, in collaboration with the Pikiran dan Jiwa Rakyat Legal Aid Institute (LBH-PIJAR), is a concrete form of social concern in developing an empowered and noble next generation. This program not only provides material support in the form of basic necessities and education, but also instills moral values, empathy, and togetherness within the community. Through a community-based approach, the assistance program serves as a means to sow hope, motivate children to have a passion for learning, and prepare them to become independent individuals and contribute positively in the future. This activity also strengthens ties between residents and fosters collective awareness that the success of the development of the next generation is a shared responsibility. This study used a qualitative descriptive approach with direct observation and interviews with administrators, donors, and beneficiaries. The results show that the assistance program not only helps meet basic needs such as food, clothing, and school supplies, but also plays a role in building self-confidence, a passion for learning, and values ​​of togetherness. This activity strengthens the social capital of residents of RW 10 Semanan as well as being an effective empowerment strategy in preparing the next generation who are moral, independent, and ready to face future challenges. With this, the author as the chairman of the implementing committee is one of the pioneers of orphanage assistance in RW 10 Semanan where there are 120 orphans from 12 RTs in the RW 10 Semanan area in collaboration with the Legal Aid Institute for the Mind and Soul of the People (LBH-PIJAR) which currently runs every month with the Majelis Madinaturassul SAW led by Al Habib Husein Bin Alwy AlHamid.